Norovirus Binding to Ligands Beyond Histo-Blood Group Antigens - Almand, Erin A.; Moore, Matthew D.; Jaykus, Lee-Ann (Frontiers in Microbiology, 2017)
Histo-blood group antigens (HBGAs) are commonly accepted as the cellular receptors for human norovirus. However, some human noroviruses have been found not to bind any HBGA ligand, suggesting potential additional co-factors. Some ligands have been found to bind noroviruses and have the potential to be additional cellular receptors/attachment factors for human norovirus or inhibitors of the HBGA interaction. The studies identifying these largely characterize different chemical, human, food or bacterial components and their effect on norovirus binding and infection, although the mechanism of interaction is unknown in many cases. This review seeks to supplement the already well-covered HBGA-norovirus literature by covering non-HBGA human norovirus ligands and inhibitors to provide investigators with a more comprehensive view of norovirus ligands.